Implementing sustainable product–service systems utilizing business model activities - Reim, Wiebke; Lenka, Sambit; Frishammar, Johan; Parida, Vinit (Elsevier, 2017)
To stay competitive and comply with government legislation, many global manufacturing companies try to diminish their environmental impact and avoid commoditization of their products by offering sustainable product–service systems (PSS). Offering PSS successfully is highly challenging, however, and significant interfirm heterogeneity exists with regard to successful PSS provision. Based on multiple case studies in two global manufacturing companies, the importance of the business model as an organizing device to align and coordinate key activities and scarce resources in PSS is highlight. The analysis provides insights into the underlying building blocks that will help firms implement a PSS business model and provides new implications for analyzing and improving PSS offers.
Keywords: product-service systems (PSS); business models; sustainability; servitization; fi=Johtaminen ja organisaatiot|en=Management and Organization|